Regulation of Nrf2 by X Box-Binding Protein 1 in Retinal Pigment Epithelium - Chen, Chen; Zhong, Yimin; Wang, Joshua J.; Yu, Qiang; Plafker, Kendra; Plafker, Scott; Zhang, Sarah X. (Frontiers in Genetics, 2018)
Normal function of the retinal pigment epithelium (RPE) is essential for maintaining the structural integrity of retinal photoreceptors and the visual process. Sustained oxidative damage of the RPE due to aging and other risk factors contributes to the development of age-related macular degeneration (AMD). The transcription factor NF-E2-related factor2 (Nrf2) is a central regulator of cellular antioxidant and detoxification responses. Enhancing Nrf2 function protects RPE cells from oxidation-related apoptosis and cell death. Previously, we demonstrated that Nrf2 activation can be induced by endoplasmic reticulum (ER) stress; however, the mechanisms are not fully understood. In the present study, we examined the role of X box-binding protein 1 (XBP1), an ER stress-inducible transcription factor, in regulation of Nrf2 in the RPE. We found that RPE-specific XBP1 conditional knockout (cKO) mice exhibit a significant reduction in Nrf2 mRNA and protein levels, along with decreased expression of major Nrf2 target genes, in the RPE/choroid complex. Using primary RPE cells isolated from XBP1 cKO mice and human ARPE-19 cell line, we confirmed that loss of XBP1 gene or pharmacological inhibition of XBP1 splicing drastically reduces Nrf2 levels in the RPE. Conversely, overexpression of spliced XBP1 results in a modest but significant increase in cytosolic and nuclear Nrf2 protein levels without affecting the transcription of Nrf2 gene. Moreover, induction of ER stress by tunicamycin and thapsigargin markedly increases Nrf2 expression, which is abolished in cells pretreated with XBP1 splicing inhibitors 4µ8C and quinotrierixin. Mechanistic studies indicate that quinotrierixin reduces Nrf2 expression likely through inhibition of protein translation. Finally, we demonstrate that overexpression of Nrf2 protected RPE cells against oxidative injury but appeared to be insufficient to rescue from XBP1 deficiency-induced cell death. Taken together, our results indicate that XBP1 modulates Nrf2 activity in RPE cells and that XBP1 deficiency contributes to oxidative injury of the RPE.